Draft Genome Sequence of the Chilean Isolate Aeromonas Salmonicida Strain cba100 - Tello-Reyes, M; Sanhueza-Chavez, L; Valdes-Parra, N; Espinoza-Cisternas, L; Espinoza-Cisternas, L (Oxford University Press, 2015)
We report the draft genome sequence from Aeromonas salmonicida sp. strain CBA100, which was characterized as an antibiotic-resistant bacterium isolated from infected rainbow trout. The total size of the genome is 4 788 109 bp, with a G + C content of 60.55%. Comparison of its open reading frames shows that the closest homologue to one third of the genes of strain CBA100 are found in A. hydrophila. The strain contains several efflux pumps and putative genes that confer resistance to multiclass antibiotics, including macrolide, β-lactamics, florfenicol and quinolones. The antibiogram profile suggests that efflux pumps are the main mechanism of resistance to non-β-lactamic antibiotics. This is the first genome of a Chilean isolate of A. salmonicida, which should shed light on the design of strain-specific vaccines against this pathogen and reduce the use of antibiotics for preventive treatment in Chilean aquaculture. © FEMS 2014.